Comparing Salivary and Dental Plaque Content of Sodium, Calcium and Phosphate after Sucrose Ingestion between Salvadora persica Sticks and Tooth Brush Users - , Wafaa Hussein Khalil; , Mohammad Yousuf Mohammad Sukkar; , Bakri Gobara Gismalla (Archives of Current Research International, 2017)
Dental caries is a biofilm-dependent oral disorder, resulting in its initiation and development from fermentable dietary carbohydrates as key environmental factors. Sucrose in particular, is considered as the most cariogenic of all carbohydrates; the biofilm forming in its presence is characterized by low concentrations of those critical ions involved in de- and re-mineralization of enamel and dentin, namely calcium, phosphates and fluoride content. Within this context, this present study aimed to compare Sodium, Calcium and Phosphate concentrations in saliva and dental plaque after sucrose ingestion among Salvadorapersica / Miswak chewing sticksusersand tooth brush users. Sixty and fifty nine adult males who were using Salvadorapersica (Miswak sticks) and tooth brush respectively were recruited in the study, excluding those who had history of smoking tobacco or smokeless tobacco, under certain medications or having chronic or oral diseases as diagnosed by oral examination. Structured face to face standardized questionnaire was performed to assess their dental and nutritional habits. Laboratory investigations were performed for salivary and dental plaque, calcium, phosphate and Na following ingestion of a cooked meal free from sucrose / containing sucrose, or after ingestion of sucrose containing drinks only. Significantly higher levels of Ca, P and Na were found after sucrose ingestion in Miswak users compared to brush users, suggesting Miswak to be an affordable anti plaque, anti cariogenic measure for providing inorganic minerals needed for re mineralization and combating drop of pH after sucrose ingestion.